The financial system, financial regulation and central bank policy - Cargill, Thomas F. (New York : Cambridge University Press, 2017)
"Traditional money and banking textbooks are long, expensive, and full of so much institutional and technical modeling detail that students cannot understand the big picture. Thomas F. Cargill presents a new alternative: a short, inexpensive book without the 'bells and whistles' that teaches students the fundamentals in a clear, narrative form. In an engaging writing style, Cargill explains the three core components of money and banking, and their interactions: 1) the financial system, 2) government regulation and supervision, and 3) central bank policy. Cargill focuses on the interaction between government financial policy and central bank policy and offers a critique of the central bank's role in the economy, the tools it uses, how these tools affect the economy, and how effective these policies have been, providing a more balanced perspective of government policy failure versus market failure than traditional textbooks"--
"Traditional money and banking textbooks are long, expensive, and full of so much institutional and technical modeling detail that students can't understand the big picture. Tom Cargill presents a new alternative: a short, inexpensive book without the "bells and whistles" that teaches students the fundamentals in a clear, narrative form. In an engaging writing style, Cargill explains the three core components of money and banking, and their interactions: 1) the financial system, 2) government regulation and supervision, and 3) central bank policy. Cargill focuses on the interaction between government financial policy and central bank policy and offers a critique of the central bank's role in the economy, the tools it uses, how these tools affect the economy, and how effective these policies have been, providing a more balanced perspective of government policy failure versus market failure than traditional textbooks"--
Includes bibliographical references and index.
Keywords: Banks and banking, Central; Finance -- Government policy; Banking law; BUSINESS & ECONOMICS / International / Economics